Characterization of Inactivated Influenza Vaccines Used in the Russian National Immunization Program - Mikhail Tarasov; Andrei Shanko; Larisa Kordyukova; Anton Katlinski (Vaccines, 2020)
Background: today’s standard quality control methods used to control the protein composition of inactivated influenza vaccines only take into account a few key reference components. They do not allow for thorough characterization of protein compositions. As a result, observation of unpredictable variations in major viral constituents and admixtures of cellular proteins within manufactured vaccines that may seriously influence the immunogenicity and safety of such vaccines has become a pressing issue in vaccinology. This study aims at testing a more sophisticated approach for analysis of inactivated split influenza vaccines licensed in the Russian Federation. The formulations under study are the most available on the market and are included in the Russian National Immunization Program. Methods: liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis, in combination with label-free protein quantitation via the intensity-based absolute-quantitation (iBAQ) algorithm, as well as a number of standard molecular analysis methods, such as sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), dynamic light scattering (DLS), and negative-stain transmission electron microscopy (TEM) were applied. Results: the methods implemented were able to identify dozens of viral and host proteins and quantify their relative amounts within the final formulations of different commercially available inactivated split influenza vaccines. Investigation of molecular morphology of the vaccine preparations using TEM revealed typical rosettes of major surface proteins (hemagglutinin and neuraminidase). DLS was used to demonstrate a size distribution of the rosettes and to test the stability of vaccine preparations at increased temperatures. Conclusions: a holistic approach based on modern, highly productive analytical procedures was for the first time applied for a series of different commercially available inactivated split influenza vaccines licensed in Russia. The protocols probed may be suggested for the post-marketing quality control of vaccines. Comparison of different preparations revealed that the Ultrix® and Ultrix® Quadri vaccines produced by pharmaceutical plant FORT LLC and trivalent vaccine Vaxigrip® produced by pharmaceutical company Sanofi Pasteur have well-organized antigen rosettes, they contain fewer admixture quantities of host cell proteins, and demonstrate good correlation among mostly abundant viral proteins detected by different methods.